Assessing Heavy Metal Contamination in Commonly Used Fertilizers for Polyculture Fish Ponds and Its Implications for Human Health: A Comprehensive Investigation - Naz, Saira; Arshad, Madeeha; Majeed, Saima; Maqaddas, Sawera; Habib, Syed Sikandar; Kesbiç, Osman Sabri; Al-Rejaie, Salim S.; Mohany, Mohamed; Bottari, Teresa; Aragona, Francesca; Fazio, Francesco (Springer Science and Business Media LLC, 2024)
Over-fertilizing fish ponds can cause pollution, introducing heavy metals into the food chain and posing health risks. The present study investigated the incidence of heavy metals (Pb, Cu, Cd, and Cr) in commonly applied fertilizers, including nitrogen, phosphorus and potassium (NPK), triple superphosphate (TSP), and di-ammonium phosphate (DAP), and their association with heavy metals in water, sediment, and cultured fish species (Catla catla, Labeo rohita, and Cyprinus carpio) in polyculture fish ponds. The study was conducted over 4 months, with four groups in triplicates: control (no fertilizer), group 1 (NPK), group 2 (TSP), and group 3 (DAP). Heavy metal analysis was carried out using atomic absorption spectrophotometry before and after fertilizer application. Significantly (p < 0.05) higher levels of heavy metals were observed in water and sediment after applying fertilizers, with the most pronounced results in group 3 (DAP) followed by group 2 (TSP). The concentration of heavy metals was significantly (p < 0.05) higher in group 3 (DAP) fertilizers compared to other groups. Compared to the control, the concentration and bioaccumulation of heavy metals were significantly (p < 0.05) higher in the fertilizer-applied groups, with notably higher levels in group 3 (DAP). Cluster analysis and the correlation matrix did not show any significant association between the heavy metals and the fertilizers, indicating a complex interplay between the biotic and abiotic factors of the system. The health index (HI) value was < 1 in fish muscles of all studied groups, indicating the fish are safe for consumption. The study recommends monitoring and regulating fertilizer use, especially DAP, to prevent heavy metal contamination, and exploring sustainable alternatives to minimize environmental and health risks.
Keywords: Fertilizer · Heavy metals · Health risk · Environmental pollution · Water · Aquaculture; Fertilizer, Heavy metals, Health risk, Environmental pollution, Water, Aquaculture